Pengaruh Profitabilitas, Transfer Pricing, dan Capital Intensity terhadap Tax Aggressiveness dengan Firm Size Sebagai Moderasi - Andi Amalia Putri; Harry Barli (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of Profitability, Transfer Pricing, and Capital Intensity on Tax Aggressiveness, with Firm Size as a moderating variable. The method used in this study is quantitative with secondary data. The population includes companies in the Consumer Cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, totaling 149 companies. Using purposive sampling, a sample of 9 companies is selected. The research applies Panel Data Regression and Moderated Regression Analysis (MRA) using EViews 12. The F-test results show that Profitability, Transfer Pricing, and Capital Intensity simultaneously affect Tax Aggressiveness. However, the t-test results show that Profitability, Transfer Pricing, and Capital Intensity each do not have a significant effect on Tax Aggressiveness. Similarly, Firm Size also does not have a significant effect on Tax Aggressiveness. The Moderated Regression Analysis (MRA) results reveal that Firm Size is not able to moderate the relationship between Profitability and Tax Aggressiveness, Transfer Pricing and Tax Aggressiveness, nor Capital Intensity and Tax Aggressiveness. This study indicates that the internal variables examined are not sufficient to explain Tax Aggressiveness behavior in the Consumer Cyclicals sector. The insignificance may be due to external factors such as government fiscal policies during the pandemic, macroeconomic fluctuations, and the conservative approach of companies in financial reporting.